2022
DOI: 10.1093/gji/ggab528
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetic indication for India–Asia collision at 12°N and maximum 810 km Greater India extent in the western suture zone

Abstract: Summary Knowing the pre-collisional extent of the northern Indian Plate margin (‘Greater India’) is vital to understanding the tectonic evolution of the India-Asia collision and the formation of the Himalayan-Tibetan orogen. However, suitable geological units for paleomagnetic investigations along the Himalayan belt are limited, which makes it difficult to reconstruct Greater India during the pre-collisional period in Late Cretaceous to Paleogene. Often the paleomagnetic results from the Zongpu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…In the western TH, a paleomagnetic study of the Paleocene/lower Eocene Dibling limestone in the Zanskar revealed a syntectonic remagnetization (best grouping at 52% unfolding) and suggested the maximum extent of Greater India was 810 ± 333 km (7.3 ± 3.0°) at 76.6°E (Figure 3 and Figure S8d of Supporting Information ) (Dannemann et al., 2022). Greater India with a 2,700 km extension was proposed based on a "Late Cretaceous" age paleomagnetic study of a section at Zhada (Meng et al., 2020); however, Xu et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the western TH, a paleomagnetic study of the Paleocene/lower Eocene Dibling limestone in the Zanskar revealed a syntectonic remagnetization (best grouping at 52% unfolding) and suggested the maximum extent of Greater India was 810 ± 333 km (7.3 ± 3.0°) at 76.6°E (Figure 3 and Figure S8d of Supporting Information ) (Dannemann et al., 2022). Greater India with a 2,700 km extension was proposed based on a "Late Cretaceous" age paleomagnetic study of a section at Zhada (Meng et al., 2020); however, Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the central–eastern TH the paleomagnetic data for the Zongshan Formation and Zongpu Formation from the Gamba area were interpreted to suggest that Greater India was 1,500–1,900 km (Patzelt et al., 1996; Yi et al., 2011). However, recent studies have questioned whether the remanence is of primary or secondary origin (e.g., Dannemann et al., 2022; Huang et al., 2017; Zhao et al., 2021), and/or a composite higher coercivity remanence was considered as a single remanence direction (e.g., Figure S7 of Supporting Information ). Therefore, these results are not considered sufficiently reliable at present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the dearth of volcanic rocks that are considered the optimum target for paleomagnetism, and the widespread thermal and chemical overprint in the Tethys Himalaya sedimentary rocks (Appel et al., 2012; Crouzet et al., 2003; Dannemann et al., 2022; Huang et al., 2017; Schill et al., 2002; Xu et al., 2022), the location of the northern edge of Greater India is more challenging to constrain than the Eurasian margin. Results from Paleocene limestones of the Tingri and Zongpu Formations were originally interpreted to suggest the Tethys Himalaya was situated 2,000–3,000 km north of cratonic India at the onset of collision (Besse et al., 1984; Patzelt et al., 1996; Tong et al., 2008; Yi et al., 2011), but these successions have since been shown to be remagnetized (Huang et al., 2017; Liebke et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Late diagenetic processes, such as clay-mineral transformations, release ions in the medium (including ferrous ions) that under the appropriate kinetic/thermodynamic conditions might lead to the growth of authigenic ferromagnetic phases (Hirt et al, 1993;Woods et al, 2002;Tohver et al, 2008). Fluid transport through the natural porosity of sedimentary rocks can induce mineral transformation, while hot basinal brines and hydrothermal associated with nearby magmatic activity/orogenies may trigger the dissolution of detrital phases and growth of others (McCabe et al, 1983;Miller & Kent, 1988;McCabe & Elmore, 1989;Jackson, 1990;Stamatakos et al, 1996;D'Agrella-Filho et al, 2000;Davidson et al, 2000;Trindade et al, 2004;Huang et al, 2017;Jiao et al, 2019;Dannemann et al, 2022;Xu et al, 2022). Finally, the maturation of organic matter and biodegradation of hydrocarbon in sedimentary basins might produce acidic solutions and disturb the local thermochemical equilibrium also contributing to the formation of new magnetic phases (Font et al, 2006;Aldana et al, 2011;Emmerton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%